2019
DOI: 10.1016/j.neubiorev.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Overlaps and distinctions between attention deficit/hyperactivity disorder and autism spectrum disorder in young adulthood: Systematic review and guiding framework for EEG-imaging research

Abstract: HighlightsThe neural basis of ADHD-ASD overlap is understudied in young adulthood (ages 16–26).We systematically reviewed relevant EEG-imaging studies (with cognitive tasks) since 2000.Seventy-five articles were identified covering seven broad neurocognitive domains.Findings suggest neural overlaps and distinctions between ADHD and ASD.Not a single study compared both disorders directly or considered dual-diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 202 publications
2
44
1
4
Order By: Relevance
“…Previous cognitive and neuropsychological findings suggested different attention impairments related to visual orienting in ADHD and ASD: the processing of alerting cues in ADHD and processing and orienting to relatively unexpected targets in ASD (Lau‐Zhu, Fritz, & McLoughlin, ). The LC‐NE system is implicated in exploiting alerting cues to increase alertness and detecting task‐relevant stimuli (Aston‐Jones, & Cohen, ; Petersen, & Posner, ), and as such in modulating the optimal attentional state during visual orienting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous cognitive and neuropsychological findings suggested different attention impairments related to visual orienting in ADHD and ASD: the processing of alerting cues in ADHD and processing and orienting to relatively unexpected targets in ASD (Lau‐Zhu, Fritz, & McLoughlin, ). The LC‐NE system is implicated in exploiting alerting cues to increase alertness and detecting task‐relevant stimuli (Aston‐Jones, & Cohen, ; Petersen, & Posner, ), and as such in modulating the optimal attentional state during visual orienting.…”
Section: Discussionmentioning
confidence: 99%
“…In ASD, atypical reorienting has instead been associated with stimulus‐locked ERP components (Sokadhze et al, ). Indeed, across studies with cognitive‐neurophysiological paradigms, altered attentional processing in ADHD most consistently relates to alerting cues; and in ASD to the relative novelty of the stimulus following a cue (Lau‐Zhu, Fritz, & McLoughlin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the ample evidence, detailed demonstration, wide recognition and discussion of the latency jitter issue in ERP research (D'Avanzo, Schiff, Amodio, & Sparacino, 2011; T. P. Knuth et al, 2006;Kutas et al, 1977;Lau-Zhu, Fritz, & McLoughlin, 2019;Ouyang et al, 2017;Sassenhagen & Bornkessel-Schlesewsky, 2015;Saville et al, 2015;, it is surprising that no well accepted tool for correcting latency jitter has come into play in the community. Researchers are still largely using trial-averaged ERP as a representation of dynamic brain response.…”
Section: General Issues and Challengesmentioning
confidence: 99%
“…There is a need to investigate specifics of the overlap and distinction in behavioral and neurophysiological impairments typical for ASD and ADHD and to determine how symptoms combine in ASD+ADHD cases (Lau-Zhu, Fritz, & McLoughlin, 2019). Reports have shown that children with ASD+ADHD present more behavioral difficulties of adaptation to daily life hassles as compared to those with ASD or ADHD alone.…”
Section: Introductionmentioning
confidence: 99%